Communicating conflicting histories - Miklošević, Željka (2011)
As a modern public institution whose scientific approach “gave voice” to artefacts and made the past an institutional form of historical discourse, the museum facilitated alienation of the past from the everyday human experience. In the context of Assmann’s theory of collective memory, it has thus been seen as a producer of cultural memory, as opposed to communicative memory created by people. Under the dominance of the modernist, one-dimensional approach to human history, museums centred their cultural messages on big topics which were presented and interpreted mainly with the aim of building or reinforcing national identity. Once modernist approach to history started to be contested, primarily by historians themselves, an opportunity arose for museum communication of prismatic, multi-perspective narratives which form a close relationship to people and, moreover, come from people. Communicative memory started to be presented in museums together with “objective” cultural memory. The museum began including people’s memories in exhibitions, adding subjectivity to historical facts. However, the juxtapositions of communicative and cultural memory inevitably give birth to oppositions, especially in the case of traumatic experiences such as those resulting from war. The paper explores the degree to which communicative memory can be subjected to institutionalization and a possibility of making museums and heritage sites polemic platforms which could contribute to reconciliation and recognition of differences.